2007
DOI: 10.1007/bf03177361
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of imperfect tips on nanoindentation by FEM

Abstract: In this paper, the imperfect tip effect of the Ti film on Si substrate on nanoindentation with Berkovich probe tip was investigated with the finite element method (FEM). In the literature, we found the effects of tip deformation and tip radius on nanoindentation were investigated frequently, but the imperfect centerline of tip has never been studied. In this work, at first, the Ti film on Si substrate was conducted with a high-resolution nanomechanical test The Young's modulus ofTi films can be obtained by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Such assumptions range from 2D equivalence of the 3D shape of the tip and angle of the pyramidal shape of the tip to most importantly the tip bluntness [12][13][14][15][16][17][18][19]. Although these assumptions may produce satisfactory results at deep indentations where the tip can be assumed ideal, inaccurate results appear at shallow indentations below 200 nm [3].…”
Section: Modeling and Simulationmentioning
confidence: 91%
“…Such assumptions range from 2D equivalence of the 3D shape of the tip and angle of the pyramidal shape of the tip to most importantly the tip bluntness [12][13][14][15][16][17][18][19]. Although these assumptions may produce satisfactory results at deep indentations where the tip can be assumed ideal, inaccurate results appear at shallow indentations below 200 nm [3].…”
Section: Modeling and Simulationmentioning
confidence: 91%
“…Attempts to account for tip rounding included empirical equations [1] and non linear fitting algorithms [2]. Chen et al [16] have also shown that the errors in the angles of a pyramidal tip will result in significantly different force curves.…”
Section: Introductionmentioning
confidence: 99%
“…The AFM can be used to directly measure the area function, rather than the actual contact area due to the elastic recovery of tested materials during withdrawal of the indenter [7,8]. Additional corrections must be made for the evaluation of the PCA due to the imperfect indenter geometry, the tilt and surface defects of samples, and the pile-up/sink-in behaviour of tested materials [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%